2019
DOI: 10.1186/s12961-019-0504-4
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Evidence Review Service (PaCERS): a knowledge transfer partnership

Abstract: The importance of linking evidence into practice and policy is recognised as a key pillar of a prudent approach to healthcare; it is of importance to healthcare professionals and decision-makers across the world in every speciality. However, rapid access to evidence to support service redesign, or to change practice at pace, is challenging. This is particularly so in smaller specialties such as Palliative Care, where pressured multidisciplinary clinicians lack time and skill sets to locate and appraise the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…The review was conducted in accordance with palliative care evidence review service (PaCERS) modified systematic review methodology. 10 This approach was developed to enable the rapid and robust assessment and reporting of clinical evidence following requests from palliative care practitioners in Wales. An initial request for this review was made by the Lead Clinician of the End of Life Care Board in Wales and the need for rapid synthesis and timely reporting during the ongoing pandemic favoured the application of this methodology.…”
Section: Methodsmentioning
confidence: 99%
“…The review was conducted in accordance with palliative care evidence review service (PaCERS) modified systematic review methodology. 10 This approach was developed to enable the rapid and robust assessment and reporting of clinical evidence following requests from palliative care practitioners in Wales. An initial request for this review was made by the Lead Clinician of the End of Life Care Board in Wales and the need for rapid synthesis and timely reporting during the ongoing pandemic favoured the application of this methodology.…”
Section: Methodsmentioning
confidence: 99%
“…The articles together provided very limited insights into the role and response of primary healthcare services in palliative care delivery during pandemics. We therefore used the pandemic response framework 15 to categorise what little data that was available into 'systems' (data that provided insights into wider healthcare systems including policy), 'space' (insights into primary healthcare delivery of palliative care in the community), 'staff' (workforce concerns) and 'stuff' (all other relevant concerns; see Table 3). 17 Systems.…”
Section: Resultsmentioning
confidence: 99%
“…This rapid review was conducted using modified systematic review methods, refined from the Centre for Reviews and Dissemination guidance for systematic reviews in healthcare 14 and informed by rapid review methods outlined by the Palliative Care Evidence Review Service, 15 with a refined review question, the search carried out within a limited set of databases, and transparency in the reporting. The structure and content of the review is informed by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…This review was conducted in accordance with the Palliative Care Evidence Review Service (PaCERS) modified systematic review methodology. 21 This review uses modified systematic review methods in which components of the review process are streamlined, in particular the time frame, which was decided upon due to the striking lack of existing literature before 2010, which was identified from a scoping search undertaken prior to the conduction of the review. The review was prospectively registered with the International Prospective Register of Systematic Reviews on 30th March 2020, ID: CRD42020176393, and is reported following the Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines.…”
Section: Methodsmentioning
confidence: 99%